The Green Ship: Reading Through Branches and Waves. Growing Outdoors with Contemporary Children's Picturebooks - Marcella Terrusi (University of Bologna, 2018)
The strong relationship between children and nature is represented in many children's picturebooks published in Italy in the last decades. In the array of picturebooks and wordless books the relationship between detail and the big picture is also displayed, as an invitation to discover connections between distant elements. In contemporary reflections about outdoor education practices, children's picturebook appear as a useful tool to involve teachers and parents in a reflection about respect of "natural rights" of children, as Zavalloni called it, such as moving around, experiencing contacts with natural elements and animals, take time to observe and feel, take risks of adventures. Nurturing a real contact with the "anima mundi" and natural rhythms is an urgent issue and challenge today, and it requires attention to life and a responsibility for collective imagination. In children's picturebooks there are places, events and symbols that can establish new paths to raise "cosmic" citizens of our planet.